2014
DOI: 10.1073/pnas.1411086111
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl tyrosine kinase promotes adipocyte differentiation by targeting PPAR-gamma 2

Abstract: Adipocyte differentiation, or adipogenesis, is a complex and highly regulated process. A recent proteomic analysis has predicted that the nonreceptor tyrosine kinase Abelson murine leukemia viral oncogene (c-Abl) is a putative key regulator of adipogenesis, but the underlying mechanism remained obscure. We found that c-Abl was activated during the early phase of mouse 3T3-L1 preadipocyte differentiation. Moreover, c-Abl activity was essential and its inhibition blocked differentiation to mature adipocytes. c-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…A proteomic analysis revealed that c-Abl was a potential key regulator of adipogenesis via regulation of the expression and activity of peroxisome proliferator-activator receptor γ 2 (PPARγ2), the master adipogenic regulator controlling adipogenesis [23,24]. These findings indicate that c-Abl participates in adipocytes metabolism regulation in vitro.…”
Section: Introductionmentioning
confidence: 96%
“…A proteomic analysis revealed that c-Abl was a potential key regulator of adipogenesis via regulation of the expression and activity of peroxisome proliferator-activator receptor γ 2 (PPARγ2), the master adipogenic regulator controlling adipogenesis [23,24]. These findings indicate that c-Abl participates in adipocytes metabolism regulation in vitro.…”
Section: Introductionmentioning
confidence: 96%
“…c-Abl is a non-receptor tyrosine kinase protein that regulates cellular proliferation and cytoskeletal remodeling (40). c-Abl is also involved in the differentiation of diverse cell types, including adipocytes, osteoblasts, and dendritic cells (41)(42)(43). The results of our study suggest that c-Abl tyrosine kinase signaling may play an important role in the differentiation of CD14 + monocytes into fibrocytes.…”
Section: Pdgf-bb-inducedmentioning
confidence: 68%
“…The associations of PPAR γ with signaling molecules including receptor and nonreceptor kinases corroborate the cross-talk function between the two signaling proteins [11, 24, 25, 30, 31]. Kumar et al (2005) identified L-tyrosine derivatives as potential PPAR α / γ inhibitors [32, 33].…”
Section: Introductionmentioning
confidence: 92%